Reformas en cuanto a castigar severamente las infracciones informáticas en la legislación penal Ecuatoriana. - Méndez Vanegas, Luis Pablo (2012)
The most important aspect of computing is information which has come to achieve a high economic value, the proper use of this information; you can create large networks of services, trade, and education and so on, supporting the development of peoples. Unfortunately in all facets of human activity, there is deceit, manipulation, greed, lust for revenge, fraud in the end the offense, which has allowed criminals to take advantage of the vulnerability of access to information communication networks of committing a series of computer crime and socio-economic equity in nature, producing harm to countless people. The Constitution of the Republic of Ecuador to refer to the laws of freedom in Article 66 paragraphs 19 and 20 provides for the protection of personal information in all its aspects, this protection includes the rights of personal freedom, which is why that personal information is considered confidential and access, dissemination and use must be authorized by the owner or the mandate of the Act, the violation is an offense it could cause irreparable damage. In the Second Book of the Penal Code in Chapter V, refers to offenses against the sanctity of the secret, determining in its Article 202 A, which. He that using any means, electronic, computer or similar, violentare keys or security systems, to access or obtain protected information contained in information systems, to undermine the secrecy, confidentiality and discretion, or simply violate the security shall be punished with imprisonment for six months to a year and a fine of five hundred thousand dollars to the United States of America ... ", also establishing some circumstances that aggravate the penalties, but they are mild to the seriousness of the offense, being necessary to punish severely those behaviors. For all the above, I have seen fit to make this thesis focused on the urgent need for reform in the Ecuadorian Criminal Code, under penalty of computer offenses in order to curb the rise in crime who commit these crimes.